إعداد الفرد المسلم سياسيا في ظلال السنة النبوية الشريفة : دراسة موضوعية تحليلية - جبه، منال أحمد (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2015)
The Islamic approach is truly an upright one, which encompasses all of life's aspects, and has achieved success in rescuing humanity and bringing it happiness, security, and stability, a fact history attests to. This is made possible by its vitality, its realistic outlook, and its suitability to the innate human disposition, as Islamic teachings guarantee the safeguarding of human society at large. The Messenger of Allah s.a.w. had employed an important approach in developing the Muslim persona politically, an approach for Muslims to follow until the time of the Hour. Thus, this dissertation seeks to discover the conception of politics and the most important Islamic political principles in the Sunnah, as well as the Prophet's s.a.w. approach in developing the Muslim persona politically, and the purpose behind it. In preparing this dissertation, the researcher utilized an inductive methodology, through which textual evidence from the Sunnah and the life of the companions relevant to the political development of the Muslim personality was extracted. The analytical method was also used to analyze prophetic texts and reveal how the Sunnah contributed to the preparation of the Muslim persona politically, as well as relating that to our present reality. The researcher came to the conclusion that a Muslim must not worship anything or anyone but Allah, and must not seek any law other than His Sharʻ (Islamic laws); and that Muslim lands should be united under one nation as it was in the early of Islam so that religion can again lead the East and the West, and would existence with justice and goodness. When that occurs, humanity will be free of repression, injustice, and corruption, and only then will bask in freedom, dignity, and honor. This will allow people a life of justice and equality, without borders separating their lands, and without a nationality or colour separating people from each other, as all will be equal in the sight of Allah, with only their taqwa (God-consciousness and piety) as a standard for comparison, not their position, tribe, colour, or status. Furthermore, there is an essential component for the success of this political system, which is the principle of shura (consultation), which is fundamental to successful political rule that subsequently engenders societal happiness and prosperity; for these reasons, Allah commanded it and ordered His Messenger s.a.w. in several instances to implement it.